Sociocultural Support Improved Safe Motherhood Practices among Mothers in Three Private Hospitals in Eastern Indonesia - Wirata, Resta Betaliani; Wahyuningsih, Nor Tri Astuti; Richard, Selvia David (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
The importance of sociocultural support from both family and health workers is very much needed by pregnant women until the postpartum period. Utilization of recording facilities using MCH books is not yet optimal in Eastern Indonesia, this is due to the lack of knowledge of midwives, compliance of health workers in filling out MCH books, absence of husbands or family members in caring for pregnant women, taking mothers for pregnancy checks, accompanying them in the birthing process. health services, considering that the mother giving birth at a